Swap : a secret history of the new Cold War - Hinshaw, Drew; Parkinson, Joe (Harper, 2025)
Swap unspools the history behind the series of prisoner trades that returned Moscow and Washington to the crude transactional logic of the Cold War, culminating in the two rivals' largest and most complex swap ever. On August 1, 2024, twenty-four people jailed in seven nations were exchanged, including eight Russian spies, smugglers, hackers, and a professional hit man. But that headline moment was only the climax of a secret war two decades in the making. --